Regenerasi Ulama di Era Digital: Tantangan Modernisasi Pesantren dan Optimalisasi Pendidikan Kader Ulama sebagai Solusi Berkelanjutan - Restu Fauzi; M.Nurul Humaidi (Global Education Journal, 2026)
The regeneration of ulama faces significant challenges amid the modernization of pesantren and the rapid advancement of digital technology. This study analyzes the dynamics between traditional pesantren education and the Pendidikan Kader Ulama (PKU) program initiated by the Indonesian Ulema Council (MUI), with a focus on digital-era adaptations. Using a qualitative library research approach, data were drawn from the foundational 2020 study by Ependi and Penggabean, supplemented by recent scholarly sources (2021–2026), policy documents, and program reports. Findings reveal persistent issues: declining mastery of classical yellow books (kitab kuning) due to curriculum shifts (70% general knowledge), accreditation problems of PTKU programs, and the erosion of ulama authority from political involvement and the rise of non-formal preachers. However, digital tools offer opportunities for hybrid learning, wider dissemination of kitab kuning interpretations, and enhanced cadre recruitment. This research proposes an optimization framework integrating digital platforms while preserving traditional values. The novelty lies in bridging historical analysis with contemporary digital solutions for sustainable ulama regeneration in Indonesia. Implications include policy recommendations for MUI, Kemenag, and pesantren leaders to strengthen formal recognition and digital integration.